2021
DOI: 10.3390/cancers13112844
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Association between Common Laboratory Tests and Overall Survival in Elderly Men with De Novo Metastatic Castration Sensitive Prostate Cancer: A Population-Based Study in Canada

Abstract: De novo cases of metastatic prostate cancer (mCSPC) are associated with poorer prognosis. To assist in clinical decision-making, we aimed to determine the prognostic utility of commonly available laboratory-based markers with overall survival (OS). In a retrospective population-based study, a cohort of 3556 men aged ≥66 years diagnosed with de novo mCSPC between 2014 and 2019 was identified in Ontario (Canada) administrative database. OS was assessed by using the Kaplan–Meier method. Multivariate Cox regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…After removing duplicates, 785 papers were screened and 40 full-text articles were selected and individually evaluated for eligibility. Finally, 19 studies were included for quantitative and qualitative analysis [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…After removing duplicates, 785 papers were screened and 40 full-text articles were selected and individually evaluated for eligibility. Finally, 19 studies were included for quantitative and qualitative analysis [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, there were no significant differences in OS, rPFS, or biochemical PFS in patients with NLR ≥ 2 from baseline with or without Abi [24]. In a Canadian study of 3556 patients with PCa and newly detected metastases, divided into five groups according to NLR values, patients with a higher NLR had a significantly increased relative risk of PCa death compared to those with a lower NLR (HR, 1.55; 95% CI, 1.27-1.90) [25]. In the study that examined the usefulness of NLR as a predictor of PCa diagnosis and disease progression, the probability of PCa metastasis was significantly increased in patients with high NLR, and the risk of metastasis was reported to be 3.2 times higher in patients with NLR > 2.5 [26].…”
Section: Discussionmentioning
confidence: 97%
“…Since the tumor microenvironment, particularly the inflammatory response, may play an important role in cancer development and progression, it has been suggested that measuring clinical factors involved in inflammation, such as CRP, albumin, and white blood cells, may predict systemic cancer progression and metastasis [20]. Among them, NLR is widely known to correlate with the prognosis of many urologic cancers, including mHSPC and CRPC [21][22][23][24][25][26]. According to a subgroup analysis of the COU302 trial, which investigated the effect of Abi in patients with mCRPC, oncological outcomes were examined using NLR 2.5 as the cutoff value [24].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have investigated the prognostic factors in CSPC patients. In a retrospective population‐based study of 3556 mCSPC patients conducted in Canada, researchers found that in multivariate analysis, the efficacy of ADT was correlated with neutrophil‐to‐lymphocyte ratio, platelet‐to‐lymphocyte ratio, and albumin, hemoglobin, and PSA decrease 17 . Briones et al .…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective population-based study of 3556 mCSPC patients conducted in Canada, researchers found that in multivariate analysis, the efficacy of ADT was correlated with neutrophil-to-lymphocyte ratio, platelet-tolymphocyte ratio, and albumin, hemoglobin, and PSA decrease. 17 Briones et al studied the survival of mCSPC patients after receiving docetaxel or abiraterone combination therapy and found that age at diagnosis of mCSPC, PSA90 at 3 months, and LATITUDE risk classification are prognostic factors of PFS. 18 However, these traditional markers all have their own limitations.…”
Section: Discussionmentioning
confidence: 99%